Migrants' remittances and economic activity - Thomas Straubhaar (Intereconomics, 1985)
The impact of migrant workers' remittances on economic activity in their home countries was long overshadowed by the manifestly positive balance of payments effect. Only gradually did it come to be recognized that it was not just the scale of remittances but also the way in which they are used that is of crucial significance for the economies of the migrants' home countries. This article estimates the contribution that such remittances made to GDP, private consumption expenditure, saving and imports in Portugal, Spain, Italy, Greece and Turkey in the period from 1960 to 1981.
Keywords: 330; Labour Migration